A adoção do voto distrital na representação política na democracia brasileira - Gennarini, Juliana Caramigo (2009)
The democracy concept retraces to the existence of a State in the form desired and assented for the people: government where the people exerts their sovereignty. The discussion concerning democracy goes beyond its conceptualization, having stronger and increasing way of incidence into its values and in the modifications of the democratic model, in compliance with the transformations of the Society and, consequently, of the State itself. The politics institutions are shaken by the complete change of its essential functions and by the discredit of the citizen-voter in the representation of its interests.